Improving Student Learning Outcomes through the CTL Model Aided by Media Pancasila Diagram - Anugraheni, Anggie Widari; Fardani, Much Arsyad; Santoso, Santoso (Lectura : Jurnal Pendidikan, 2024)
This research is based on low students’ learning outcomes. The purpose of this study is to improve the learning outcomes of grade V students of elementary school (Sekolah Dasar Negeri/SDN) 8 Gondosari using the Contextual Teaching and Learning model assisted by Pancasila diagram media. This research was a classroom action research. This research was done in two cycles. The subject of this research was 17 students of class V SDN 8 Gondosari. The data was collected through interview, observation, and writing test. The data was analyzed qualitatively and quantitatively. The results of the first cycle showed the percentage of 64.71%. For the second cycle, the percentage was 88.24%. Meanwhile, the results of interviews and observations obtained from teachers and students, namely for teacher skills in the first cycle, obtained a score of 66%, while in the second cycle 92% for student learning activities in the first cycle with a score of 58%, there was an increase in the second cycle of 73%. Based on these findings, it can be concluded that the use of Contextual Teaching and Learning model assisted by Pancasila diagram media can improve the learning outcomes of grade V students of SDN 8 Gondosari.